PENGARUH SERTIFIKASI GURU DALAM MENINGKATKAN KOMPETENSI PEDAGOGIK DI UPTD SD NEGERI 122340 PEMATANGSIANTAR - Simanjuntak, Melvin; Nitalin Cindy Siahaan; Nabila Hasmardani Damanik; Safitri Maretty Lumbanbatu; Arum Nirmala; Anita Lasmaria Rajagukguk; Bhaktiven Aryan Rumahorbo; Daniel Andriando Saragih (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the impact of the teacher certification policy on improving teacher performance at UPTD SD Negeri 122340. Teacher certification is a strategic government step to ensure that teachers have adequate pedagogical competence, including mastery of learning theory, curriculum development, lesson planning, and evaluation of learning outcomes. This study uses a descriptive quantitative method with questionnaires involving all teachers in the school as respondents. The findings reveal that the teacher certification program positively impacts professionalism and performance, particularly in mastering student characteristics and conducting educative teaching processes. Furthermore, certification motivates teachers to innovate in teaching methods and actively participate in professional training. However, several challenges, such as limited resources and bureaucratic hurdles, were identified. Communication, teacher attitudes, and institutional support are critical factors influencing the program's success. These findings emphasize the need for optimizing the certification program to ensure equitable improvement in educational quality.